Konsentrasi Protein Total, Albumin, dan Globulin Anak Kambing Peranakan Etawah Setelah Pemberian Berbagai Sediaan Kolostrum* (TOTAL PROTEIN, ALBUMIN, AND GLOBULIN CONCENTRATIONS ON ETTAWAH CROSSBREED NEONATES FOLLOWING THE ADMINISTRATION OF VARIOUS FORM O - Esfandiari, Anita; Widhyari, Sus Derthi; Widodo, Setyo; Wibawan, I Wayan Teguh; Sajuthi, Dondin; Sutama, I Ketut (Jurnal Veteriner; Vol 15 No 3 (2014), 2014)
This experiment was conducted to study the profile of total protein, albumin, and globulin concentrationson Ettawah crossbreed neonates after consuming various colostrums. Twenty four healthy neonatal kidswere used in this study. The neonates were divided into four groups. Each group received fresh maternal(goat) colostrum, frozen-thawed bovine colostrum, bovine spray dried colostrum, and bovine powdercommercial colostrum, respectively. Colostrums were given at 10% of body weight directly after birth andfollowed by the same amount every 12 hours, for three days. The blood was taken from jugular vein at 0, 12,24, 48, 72, and 168 hours after birth to determine total protein, albumin, and globulin concentrations.Results of this study indicated that the serum total protein and globulin concentration increased andreached the peak at 24 hours after birth. Compared to the concentration at birth, the increase of totalprotein concentration were 62.77%, 59.26%, 48.05%, and 66.67% in fresh maternal (goat), frozen-thawedbovine, bovine spray dried, and commercial bovine colostrum, respectively. Serum globulin concentrationincreased 4.9, 4.4, 4.8, and 14.6 times in fresh matermnal goat, frozen-thawed bovine, spray dried, andcommercial bovine colostrums respectively, compared to the concentration at birth. In conclusion, theconsumption of various colostrums i.e. fresh maternal goat colostrums, bovine colostrums (frozen-thawed,spray dried and commercial colostrums) would increase the concentration of blood total protein and globulin,which both reached the highest concentration at 24 h after birth.
Keywords: total protein, globulin, neonatal kids, fresh maternal goat colostrums